Effects of Cu addition on low temperature ordering of FePt films with nanocolumn-like granular structure. (July 2014) - Wu, B.; Yu, Y.; Bi, X.
<x content-type="archive" xml:space="preserve">Abstract</x> (FePt)1−xCux (x = 0, 7·9, 16·0, 22·9 at-%) films 140 nm thick were deposited on glass substrates by cosputtering of FePt target and Cu chips. The Cu content was adjusted by changing the number of Cu chips. Microstructures of the films were studied by XRD and cross-sectional TEM observations. The (FePt)1−xCux thin films annealed at various temperatures for 20 min were characterised by nanoscale column-like granular structure with a height of ∼140 and lateral size of 5–10 nm. Each granule presented a polycrystalline structure of low angle grain boundaries, being much different from conventional column-like granular films. The FePt film containing 16·0 at-%Cu exhibited a high ordering parameter of 0·73, leading to a great increase in coercivity. The Cu addition was found to promote low temperature ordering of the films, which is discussed in combination with the nanoscale column-like granular structure in the films.